The Influence Of Work Discipline And Supervision On Work Performance With Job Satisfaction As A Mediating Variable At The South Binjai Sub-District Office - Salamudin; Mesra B (Yayasan Multidimensi Kreatif, 2025)
Effective work discipline and supervision are expected to increase job satisfaction, which in turn has an impact on improving work performance. This study aims to analyze the influence of Work Discipline and Supervision on employee work performance mediated by job satisfaction at the South Binjai District office. Data was obtained through a survey with a quantitative approach and analyzed using the Partial Least Squares (PLS) method with a sample of 117 employees. The results of the hypothesis test showed that work discipline and supervision had a positive and significant effect on Work Performance, with T-Statistics of 3,589 and 6,264, respectively, and P-Value < 0.05. This shows that increased discipline and supervision will improve employee work performance. In addition, work discipline and supervision also had a positive effect on Job Satisfaction, with T-Statistic values of 5,266 and 4,842. Job Satisfaction was proven to have a significant positive influence on Job Performance, with a T-Statistic of 8,140, showing the important role of Job Satisfaction in driving employee performance. The results of the indirect influence test show that Supervision and Supervision have a significant effect on Job Performance through Job Satisfaction as a mediator. The indirect influence of Work Discipline and Supervision on Work Performance through Job Satisfaction had T-Statistics of 4.920 and 3.637 > 1.96, respectively, and P-Value < 0.05 < 0.05. These findings indicate that the influence of these two variables on Job Achievement is more effective when facilitated by high Job Satisfaction.